Defective cytotoxic lymphocyte degranulation in syntaxin-11–deficient familial hemophagocytic lymphohistiocytosis 4 (FHL4) patients - Bryceson, Yenan T.; Rudd, Eva; Zheng, Chengyun; Edner, Josefine; Ma, Daoxin; Wood, Stephanie M.; Bechensteen, Anne Grete; Boelens, Jaap J.; Celkan, Tiraje; Farah, Roula A.; Hultenby, Kjell; Winiarski, Jacek; et al. (Blood, 2007)
Familial hemophagocytic lymphohistiocytosis (FHL) is typically an early onset, fatal disease characterized by a sepsislike illness with cytopenia, hepatosplenomegaly, and deficient lymphocyte cytotoxicity. Disease-causing mutations have been identified in genes encoding perforin (PRF1/FHL2), Munc13-4 (UNC13D/FHL3), and syntaxin-11 (STX11/FHL4). In contrast to mutations leading to loss of perforin and Munc13-4 function, it is unclear how syntaxin-11 loss-of-function mutations contribute to disease. We show here that freshly isolated, resting natural killer (NK) cells and CD8+ T cells express syntaxin-11. In infants, NK cells are the predominant perforin-containing cell type. NK cells from FHL4 patients fail to degranulate when encountering susceptible target cells. Unexpectedly, IL-2 stimulation partially restores degranulation and cytotoxicity by NK cells, which could explain the less severe disease progression observed in FHL4 patients, compared with FHL2 and FHL3 patients. Since the effector T-cell compartment is still immature in infants, our data suggest that the observed defect in NK-cell degranulation may contribute to the pathophysiology of FHL, that evaluation of NK-cell degranulation in suspected FHL patients may facilitate diagnosis, and that these new insights may offer novel therapeutic possibilities.